2018
DOI: 10.1002/minf.201800025
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Models for HOMO and LUMO Energies of N‐Donor Heterocycles as Ligands for Lanthanides Separation

Abstract: Quantum chemical calculations combined with QSPR methodology reveal challenging perspectives for the solution of a number of fundamental and applied problems. In this work, we performed the PM7 and DFT calculations and QSPR modeling of HOMO and LUMO energies for polydentate N-heterocyclic ligands promising for the extraction separation of lanthanides because these values are related to the ligands selectivity in the respect to the target cations. Data for QSPR modeling comprised the PM7 calculated HOMO and LUM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
(79 reference statements)
1
4
0
Order By: Relevance
“…the MAE/RMSE for the external test reaches a maximum of 0.4 eV for HOMO energies and 0.2 eV for LUMO energies, as seen from Figure 3. The training/test data contains cations of the same alkyl chain length and position, 37 Karpov et al reported similar deviations as this study for external test casewith RMSE between 0.17 -0.26 eV for HOMO/LUMO 38. …”
supporting
confidence: 78%
“…the MAE/RMSE for the external test reaches a maximum of 0.4 eV for HOMO energies and 0.2 eV for LUMO energies, as seen from Figure 3. The training/test data contains cations of the same alkyl chain length and position, 37 Karpov et al reported similar deviations as this study for external test casewith RMSE between 0.17 -0.26 eV for HOMO/LUMO 38. …”
supporting
confidence: 78%
“…Most machine learning models developed for HOMO–LUMO gaps have been those for organic structures. For example, Zheng et al have previously created machine learning models for benzenoid polycyclic hydrocarbons. Also for organic compounds, von Lilienfeld and co-workers developed models with prediction errors of ∼0.1 eV and showcased methods for achieving improved data efficiency, which is often problematic in HOMO–LUMO gap models. Zhang and Aires-de-Sousa created a B3LYP structure and HOMO and LUMO energy database for tens of thousands of organic structures and then trained a variety of machine learning models and found accuracy up to 0.15 eV.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The structures of hesperidin, naringin and myricetrin were optimized by quantum chemistry calculation methods to obtain a reasonable substrate structure. Molecular orbital theory indicates that the distribution of the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) plays a key role in the occurrence of molecular reactions (Solov’ev et al 2018 ). Figure 4 A shows the distribution of the frontier molecular orbitals of the three substrates.…”
Section: Resultsmentioning
confidence: 99%